The future teachers‟ training to communicative-speech development of junior schoolchildren - Liudmyla Matsuk (Vasyl Stefanyk Precarpathian National University, 2017)
The article outlines the main stages of future teachers' training to communicative-speechdevelopment of junior schoolchildren. In particular it is defined that among the subjects ofinitial school course the decisive role in training, education and personal development ofjunior schoolchildren belongs to native language. Because exactly their success in masteringthe knowledge of all other subjects, the growth of overall development, raise of the culturallevel, expanding of view will depend on abilities and skills of the native language. Key words: future teachers' training, language competence, competence, juniorschoolchildren, native language, abilities, knowledge, skills.